Single‐blind randomized controlled trial of surfactant vs hypertonic saline irrigation following endoscopic endonasal surgery. Issue 4 (20th November 2012) - Farag, Alexander A.; Deal, Allison M.; McKinney, Kibwei A.; Thorp, Brian D.; Senior, Brent A.; Ebert, Charles S.; Zanation, Adam M.
<x xml:space="preserve">Abstract</x> Background Recent discussion has revolved around formulations of irrigation in the postoperative functional endoscopic sinus surgery patient, specifically the efficacy of emulsion based nasal irrigations. Methods Forty adult candidates for endoscopic endonasal surgery with chronic rhinosinusitis (CRS) were prospectively randomized. The 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and 31‐item Rhinosinusitis Outcome Measure (RSOM‐31) quality of life assessments, as well as a phenyl ethyl alcohol (PEA) smell threshold test were obtained preoperatively and over 3 postoperative visits in a 4‐month period. Repeated measures analyses and Fisher's exact tests were used to assess statistical differences. Results Of the 40 patients enrolled, 33, 32, and 26 patients were seen at postoperative visits 1, 2, and 3, respectively. The surfactant (S) and hypertonic saline (HS) irrigation groups both showed significant decreases in scores for both the SNOT‐22 and RSOM‐31 over time (both p < 0.0001), but no difference was seen between the 2 groups (p = 0.09, p = 0.5). PEA thresholds showed overall improvement in both groups 3 to 4 months after surgery: 62% (8/13) of HS patients and 50% (6/12) of S patients, but did not differ between the groups (p = 0.3). The S group reported significantly more side effects (52% vs 6%, p = 0.002) and had more patients stop the solution (20% vs 0%) and fewer S patients finished the study compared to the HS group. Conclusion There were no significant differences in overall subjective symptoms related to sinonasal disease between S and HS irrigation, but tolerability appeared to be an issue. More patients reported side effects with S irrigation, and 20% receiving S irrigation stopped the solution, compared to none receiving HS irrigation.